Analisis aktivitas belajar daring siswa pada mata pelajaran ips terpadu di kelas VIII A SMP Negeri 1 Ngabang Kabupaten Landak - Ananda Yuniar; Suherdiyanto Suherdiyanto; Paiman Paiman (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
The techniques used in this research consist of direct communication techniques, indirect observation techniques, and documentary study techniques. Based on the results of research that has been carried out: 1) Planning for online learning activities for students in Integrated Social Studies subjects in class VIII A at SMP Negeri 1 Ngabang: The ability to make teaching preparations is the first step that must be possessed by teachers, and as the estuary of all theoretical knowledge, and a deep understanding of learning objects and learning situations, so it can be concluded that a very important and very decisive part of achieving the learning objectives itself with the learning plan itself can create a learning process that is expected to run well and directed. 2) Students' online learning activities in Integrated Social Studies subjects in class VIII A at SMP Negeri 1 Ngabang, have been going well as for indicators including: a) Visual Activities, b) Oral Activities, c) Listening Activities, d) Writing Activities, e) Drawing Activities, f) Motor Activities, g) Mental Activities, h) Emotional Activities. 3) Obstacles to the implementation of students' online learning in Integrated Social Studies subjects in class VIII A at SMP Negeri 1 Ngabang: (1) Lack of student awareness or students' intention to take part in learning. (2) Difficulty dealing with students who are not active in learning. (3) Inadequate student quotas and many other obstacles such as student permission to teachers regarding health, so that not all students take part in the zoom. (4) The enthusiasm of students in participating in online learning is also an obstacle, so that students' understanding of the material provided by the teacher has not been categorized as optimal